2005
DOI: 10.1097/01.mco.0000172576.48772.a8
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional treatment of bone fracture

Abstract: Recent supplementation studies appeared to be underpowered or suffered logistic problems, but previous recommendations for multinutrient feeding in hip fracture aftercare remain. Supplementation trials of higher scientific quality are needed, and enteral feeding, anabolic treatment and multimodal approaches need to be evaluated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…2005). Mortality and postoperative complications decreased for this patient group when they received nutritional supplements (Cederholm & Hedström 2005, Eneroth et al. 2006).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…2005). Mortality and postoperative complications decreased for this patient group when they received nutritional supplements (Cederholm & Hedström 2005, Eneroth et al. 2006).…”
Section: Introductionmentioning
confidence: 80%
“…In the present study, 8·7% of the patients developed nosocomial infections in the intervention group compared with 18% in the control group ( p = 0·137). Studies by Cederholm and Hedström (2005), Langer et al. (2003) and Avenell and Handoll (2006) have shown that postoperative complications decreased when patients received nutritional supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Nandrolone as a doping agent is widely abused to improve athletic performance and body image (Hemmersbach and Große, 2010;Lumia and McGinnis, 2010). Nandrolone is also used medically as a treatment for anemia and other diseases (Cederholm and Hedström, 2005;Deicher and Hörl, 2005). Several studies reported the presence of nandrolone in wastewater, and even the level exceeded 60 ng/L (Backe et al, 2011;Sun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…W wa run kach po pu la cji pol skiej, u cho rych do ro słych, w trak cie go je nia zła mań ko ści, optymal nym po stę po wa niem jest za tem su ple men ta cja wap nia i wi ta mi ny D w daw kach od po wied nio 1200 mg/d (u osób z ma są cia ła po wy żej 100 kg w dawce więk szej, na wet 1500 mg/d) oraz 2 000 (u otyłych 4 000, a w znacz nych, prze wle kłych nie do borach zdiagnozowanych oznaczeniem stężenia witaminy D w surowicy krwi (<20 ng/ml), na wet do 10 000 j.m./d), przy czym po win na być ona za le cana wraz z od po wied nią die tą (pro duk ty mlecz ne, na biał, ry by) i po wstrzy my wa niem się od sto so wania uży wek (pi cie moc nej ka wy, her ba ty i cze ko lady, pa le nie ty to niu i pi cie al ko ho lu), opty mal nie z za cho wa niem umiar ko wa ne go wy sił ku fi zycz nego i eks po zy cją skó ry na pro mie nio wa nie sło neczne [57,58]. Za le ce nia te, sto so wa ne przez ca ły okres go je nia zła ma nia wraz z prze bu do wą tkan ki kostnej, wy no szą cym mi ni mum 6 mie się cy (do 2 lat) po zła ma niu, po zwo lą na peł ne po kry cie za po trze bowa nia or ga ni zmu na wapń i wi ta mi nę D w okre sie two rze nia zro stu kost ne go i na stęp nie je go re mode lo wa nia.…”
Section: Podsumowanieunclassified